Validation of Chronocancer camilosantanai† Santana, Tavares, Martins, Melo & Pinheiro (Crustacea, Decapoda, Brachyura) from the Romualdo Formation, Araripe Sedimentary Basin, Brazil - William Santana; Marcos Tavares; Carlos Antônio Muniz Martins; José Patrício Pereira Melo; Allysson P. Pinheiro (Papéis Avulsos de Zoologia, 2023)
Abstract Santana et al. (2022) described a new genus and species of fossil crab, Chronocancer camilosantanai, from carbonate concretions of the Romualdo Formation of the Araripe Sedimentary Basin. The journal in which the description appeared was published online only and the new name did not include a ZooBank registration number (LSID), as required for validation of new names in electronic-only publications. The present note serves to validate the name Chronocancer camilosantanai by fulfilling the ICZN conditions for nomenclatural availability. The date and authorship of the specific name, accordingly, are those of this note, not Santana et al. (2022).